A one-step carbonization route towards nitrogen-doped porous carbon hollow spheres with ultrahigh nitrogen content for CO2 adsorption1. Issue 62 (11th August 2015) - Wang, Yu; Zou, Houbing; Zeng, Shangjing; Pan, Ying; Wang, Runwei; Wang, Xue; Sun, Qingli; Zhang, Zongtao; Qiu, Shilun
<x xml:space="preserve">Abstract</x> N-doped porous carbon hollow spheres with an ultrahigh nitrogen content of 15.9 wt% and a high surface area of 775 m2 g−1 were prepared using MF nanospheres as hard templates and nitrogen sources.